A Recent Approach: Melatonin Avoids Anatomofunctional Changes Associated to Aging in a Rat Model - Gómez, Bertha Prieto; Reyes-Vázquez, Cruz; Velázquez-Paniagua, Mireya (Highlights on Medicine and Medical Research Vol. 4, 2021)
Melatonin is a hormone synthesized and released primarily by the pineal gland. Its secretion follows a circadian rhythm with a peak overnight. Melatonin is a natural hormone secreted in humans with a circadian rhythm, its values increase during the darkness. Its secretion is initiated approximately to the three months of age and continues to rise during the childhood. Previous to the puberty there is a decrease of melatonin secretion that continues until the old age. Melatonin has effects in the body and acts through at least four mechanisms: Membrane receptors, orphan nuclear receptors, calmodulin and free radicals. The melatonin amount varies according to age. Infants younger than three months of age secrete very little melatonin. It has been suggested that aging can be a consequence of the oxidation of cells that eventually become vulnerable to injury and die. This work reviews the antioxidant effects of melatonin in a rodent model, on the formation of free radicals, on the MAP2 protein expression and on the electrophysiology of the hippocampus at different ages. The results indicate that melatonin maintains in a “best” state to the experimental animals compared to controls. It suggests the use of melatonin as a therapy to prevent or delay the aging effects on the cells.